A Postmodern Accounting Theory : an Institutional Approach - Breton, G. (Gaétan) (Emerald Publishing Limited, 2019)
Drawing upon frameworks employed in the human sciences, Breton builds a multi-faceted theory of accounting, conceiving it as a fundamentally social activity that puts preparers of financial statements in contact with users in order to help them make economic decisions, and analyzing the behavior of preparers and users.